Completeness of revascularization by FFRCT and prognosis in stable chest pain. (3rd October 2022) - Madsen, K T; Noergaard, B L; Oevrehus, K A; Parner, E; Jensen, J M; Grove, E L; Fairbairn, T A; Nieman, K; Patel, M; Rogers, C; Mickley, H; Rohold, A; et al.
Abstract: Introduction: Major randomized trials of patients with stable chest pain (CP) demonstrated no prognostic benefits of coronary revascularization over optimal medical treatment (OMT). However, in a recent large-scale study, completeness of revascularization was associated with a reduced risk of all-cause death and non-fatal myocardial infarction (MI). Purpose: To evaluate the association between completeness of revascularization relative to the result of coronary CT angiography (CTA) derived fractional flow reserve (FFRCT) and 3-year prognosis in patients with new onset stable CP and coronary stenosis. Methods: Multicenter cohort 3-year follow-up sub-study of 900 patients from the Assessing Diagnostic Value of Non-invasive FFRCT in Coronary Care (ADVANCE) registry at three Danish sites, the "ADVANCE-DK Registry". All patients had at least one ≥30% coronary stenosis by CTA and underwent subsequent core laboratory FFRCT analysis by HeartFlow. The FFRCT result was abnormal when ≤0.80 (2 cm distal to stenosis). Patients were classified according to completeness of revascularization by FFRCT: 1) completely revascularized (CR-FFRCT), all coronary arteries with an abnormal FFRCT test result revascularized; 2) incompletely revascularized (IR-FFRCT), ≥1 coronary artery with an abnormal FFRCT test result not revascularized. The primary endpoint (PE) was a composite of all-cause death and spontaneous MI. The secondary endpoint (SE) was a composite of cardiovascular (CV) death and spontaneous MI. Results: Patient characteristics are given in Table 1. In total 36 (4.0%) patients suffered a PE (all-cause death, n=24; MI, n=12) and 22 (2.4%) an SE (CV death, n=10; MI, n=12). Overall, an abnormal vs a normal FFRCT test result was associated with an increased risk of both the PE, 6.6% vs 2.1%, relative risk (RR): 3.1; 95% CI: 1.6–6.3, p<0.001 and of the SE, 5.0% vs 0.6%, RR: 8.7; 95% CI: non assessable, p<0.001. In patients with abnormal FFRCT, revascularization vs no revascularization did not reduce the risk of the PE or the SE (data not shown). Patients with IR-FFRCT vs CR-FFRCT had a numerical, but not statistical significantly, increased risk of the PE, 8.6% vs 4.2%, RR: 2.14; 95% CI: 0.87–5.26, p=0.10), and an increased risk of the SE, 7.1% vs 2.4%, RR: 3.13; 95% CI: 1.02–9.63, p=0.04, Figure 1. In CR-FFRCT versus normal FFRCT no difference in the risk of the PE or the SE was observed, Figure 1. Univariate sensitivity analyses performed in the IR-FFRCT group did not reveal any differences in the risk of the PE or the SE after adjustment for neither statin therapy at follow-up (−/+), baseline risk variables (< / ≥3), amount of CAC (< / ≥400), degree of stenosis by CTA (< / ≥50%) nor referral to ICA (−/+). Conclusion: In symptomatic patients with coronary stenosis by CTA, incomplete revascularization determined by FFRCT is associated with an increased risk of adverse cardiovascular outcomes compared to complete revascularization. Funding Acknowledgement: Type of funding sources: None.